KEPRIBADIAN GURU PERSPEKTIF ISLAM - Indah Esti Hijriyah (BRIGHT VISION Journal of Language and Education, 2022)
This study wants to describe the personality of the Islamic perspective teacher. This study uses a qualitative approach of literature study. The results show that a Muslim should have a noble personality that distinguishes himself from others, especially if he is an educator, because in fact the educator is a person who can be used as a role model and example by the person who is educated, so he must be able to maintain his attitude and behavior so that he does not fall into attitudes or actions that degrade or eliminate his glory,  Thus an educator must have a personality that distinguishes himself from others. Therefore, it has become a must for every Muslim and Muslim educator to read, understand and practice it in the world of education that he is engaged in and pursues.Keywords: Personality, Teacher, Islam